Botox or the new face of the fight against depression - literature review - Nowińska, Martyna; Kozyra, Magdalena; Raczkiewicz, Przemysław; Kaczerska, Marlena; Śmiech, Natalia; Milanowska, Joanna (Journal of Education, Health and Sport, 2021)
Introduction: Depression is a common psychiatric disorder leading to high burden especially for some other psychiatric comorbidity. Annually over 43 billion dollars are expended for patients with depression among them 28% are directly for depression and other costs are related to mortality and morbidity due to depression. The aim of the study: Paying attention to new options for treating depression – a disease that affects more and more people. Material and method: The research was done by the usage of the PubMed and Google Scholar articles about the topic of: botulinum toxin; depression; treatment. Description of the state of knowledge: Injecting Botox into the muscles responsible for expression of anguish or sadness may potentially decrease the patients experience of feelings. Botox reversibly blocks acetylcholine release from neuronal axons into the synapse, inhibiting neuromuscular transmission. If the facial feedback hypothesis is correct, by injecting Botox into the corrugator and procerus muscles, it will reversibly inhibit frown facial expressions and have the capability of propagating or enhancing sad and depressed feelings. Summary: The results from all randomized control trials proved that botulinum toxin A injection in the glabellar region was associated with significant improvement mood and may be a safe and effective treatment to reduce symptoms of depression.